Awareness of Digital Competences among Student Teachers - A Mixed-Methods Study on the Role of Seminars Promoting Digital Competences - Bärnreuther, Cindy (Proceedings of EdMedia + Innovate Learning, 2024)
This study is explicitly dedicated to the (non-)awareness of digital competences among prospective teachers. The study comprised a sample of N = 127 participants and was conducted from April 2023 to July 2023. Quantitative data was collected using the "SELFIEforTEACHERS" self-assessment tool, while parallel qualitative data was collected using the Thinking Aloud method (N = 9). Frequency analyses were carried out for the quantitative evaluation of the data, as well as t-tests for independent samples to investigate differences between students who attended courses with a media education focus and those who did not. In a mixed-method approach, the results of the quantitative data were analysed in depth using statements in the qualitative data. The results show that, despite a certain awareness of their digital competences, student teachers often rate themselves at lower levels of competence. Participation in events to promote digital skills appears to increase awareness of these skills. Furthermore, there are indications of differences in awareness of digital competences between students who have attended such events and those who have no